2010
DOI: 10.1002/jsc.858
|View full text |Cite
|
Sign up to set email alerts
|

Strategic thinking in family businesses

Abstract: Certain strategic issues and challenges relating to financing and capital structure in family businesses are thought of differently from non‐family businesses and lead them to employ specific financial policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Despite longer working hours in copreneurship relations here studied, efforts will be rewarded by the sustainability, success and longevity of the firm and the business (Fletcher et al , 2009; O’Regan et al , 2010). Nicolas (2011) also reported that shared trust becomes implicit in copreneurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite longer working hours in copreneurship relations here studied, efforts will be rewarded by the sustainability, success and longevity of the firm and the business (Fletcher et al , 2009; O’Regan et al , 2010). Nicolas (2011) also reported that shared trust becomes implicit in copreneurs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the significant economic power of copreneurial family firms in the world (Dyer et al , 2013) and the lack of studies on the family dynamics of this type of business (O’Regan et al , 2010; Fletcher et al , 2009) and gender theory (Chrisman and Patel, 2012; Diaz-Garcia and Brush, 2012; Jimenez, 2009; Kim and Gao, 2013), principally in the context of developing countries such as Brazil, this study contributes both to developing knowledge in this area and to showing the factors to consider in this type of firm created and managed by couples. The results of the study will provide useful insights into copreneurial businesses from the family dynamics and gender perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However according to Liedkta's model, strategic thinking is an individual initiative where an individual can be influenced by the organisational context in which he operates (Graetz, 2002). While Bonn, (2001) argues that strategic thinking at individual level is composed of three main elements namely: holistic understanding of the organisation and its environment, degree of creativity, innovative solutions to issues that challenge existing approaches and thinking and lastly the vision of the future, inspiring and uniting people in the achievement of the corporate goals (O'Regan, Hughes, Collins, & Tucker, 2010). Nadkrani and Barr, (2008) in adressing the question on what drives strategic action offered an explanation based on two views: the managerial cognition view and industry structure view.…”
Section: The Construct Tmt Cognitionmentioning
confidence: 99%